PENERAPAN MODEL COOPERATIVE LEARNING TIPE JIGSAW UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN MATEMATIS SISWA KELAS V SEKOLAH DASAR - Waluyo Waluyo (Integral : Pendidikan Matematika, 2017)
The background of this study low quality of students' mathematics learning outcomes, such as low learning achievement, passive student learning activities, the use of props and less innovative instructional media, and the selection of instructional models that teachers are less innovative. The purpose of this study was to determine the increase in the ability of students' mathematical understanding, knowing the increased interest and motivation to learn mathematics, and determine the increase mathematics learning activities congruency and symmetry concepts with the application of Cooperative Learning Jigsaw, as well as determine the increase the ability of teachers in teaching and learning mathematics. Place of research at SDN 1 Panonganlor Cirebon by the number of students 30 people in the 1st half of the school year 2016/2017. Mathematics courses with competence congruency and symmetry. Acting as a colleague a sixth grade teacher in the same school with the author, students who studied his ability is very heterogeneous. PTK consists of three cycles, with each cycle includes the stages of planning, action, observation and reflection. The research instrument is an evaluation test sheet mathematics student learning ability, interest and motivation observation sheet student learning and student activity observation sheet and the sheet observation ability of teachers in the learning process. Technical analysis of the data using interactive analysis, consisted of data reduction, data presentation and conclusion. Results of the study are: 1). An increase in the ability of the students' understanding of mathematics learning in the first cycle = 70.87 (66.67%) and the second cycle = 82.2 (100%), the average increase in value of 11.33 (33.33%), 2) enhancing students' interest and motivation cycle I = 65.6% and cycle II = 89.6% increase (24%). 3) improvement of student learning activities = 72.57% the first cycle and the second cycle = 92% (increase = 19.43%), 4). increased capacity in the management of the learning process cycle I = 70% and the second cycle of 90% (up 20%). Keywords: Cooperative Learning Model Jigsaw mode and Mathematical Understanding Capabilities.